A newly isolated organic solvent tolerant Bacillus sphaericus 205y producing organic solvent-stable lipase - Hun, Chin John; Raja Abd Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran (Elsevier Science B.V., 2003)
A total of 131 organic solvent tolerant isolates originating from soil samples were successfully isolated via direct plating method using 1% (v/v) of either benzene, toluene, or mixture of benzene and toluene as their sole carbon source. Six isolates demonstrated high tolerance of up to 75% (v/v) concentration of BTEX (n-benzene, toluene, ethyl benzene and p-xylene). These isolates were screened for lipolytic activity using triolein plates. Isolate 205y was found to produce the highest lipase yield in liquid medium and later identified as Bacillus sphaericus by biochemical test and 16S ribosomal DNA sequence. No work on B. sphaericus producing lipase has been reported so far. Four production media were tested and medium M3 yielded the highest lipase activity of 0.42 U ml-1 min-1 at 36 h incubation time. Stability studies in various organic solvents at 25% (v/v) showed that lipase from B. sphaericus 205y were not only stable but also activated by n-hexane and p-xylene by 3.5- and 2.9-folds, respectively. The activity, however, was greatly reduced in dimethyl sulfoxide and was completely inactivated by hexadecane and acetonitrile.